The Use of Local Tourism Pictures as Learning Media to Enhance Students’ Motivation and English Vocabulary Mastery - Yizrel Nani Sallata; Viktor Siumarlata; Selvina Songlo; Alfiani Romanita Taruk (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study investigates the effect of using local tourism pictures as English learning media on students’ vocabulary mastery and learning motivation at the elementary level. The research was motivated by the persistent challenges Indonesian learners face in understanding, memorizing, and retaining English vocabulary, which often leads to low motivation and limited engagement. A quantitative one-group pretest–posttest design was employed, involving 21 fifth-grade students from UPT SDN 14 Mengkendek, South Sulawesi. Vocabulary and motivation data were collected through pre- and post-tests and analyzed using paired-sample t-tests. Results revealed significant improvements in both vocabulary mastery (M = 52.62 to 72.14, p < .001) and learning motivation (M = 44.81 to 53.10, p < .001). These findings suggest that the use of local tourism images—such as Torajan landmarks—effectively supports vocabulary retention and fosters a stronger emotional connection to learning materials. The integration of culturally relevant visual media aligns with the principles of Contextual Teaching and Learning (CTL) and Self-Determination Theory, showing that when students learn through familiar, locally grounded visuals, they become more motivated and engaged. Overall, the findings contribute to English language education for young learners by providing empirical evidence that culturally relevant, contextual, and visual materials enhance learners’ engagement, comprehension, and motivation, and by offering practical pedagogical insights for teachers in designing culturally responsive and meaningful English learning materials at the primary school level.